World War II (1939-1945) Oceanographic Observations - S Levitus; S Matishov; I Smolyar; O K Baranova; M M Zweng; T Tielking; N Mikhailov; S Kizu; F Nast; G Reed; R Keeley; L Rickards; et al. (Data Science Journal, 2013)
We document the geographical and temporal distributions of oceanographic vertical profile observations made during World War II (1939-1945) that are included in the " World Ocean Database " (WOD). The WOD is a product of the NOAA/National Oceanographic Data Center, USA and its co-located ICSU World Data Center for Oceanography. The WOD is the largest collection of ocean profile data available internationally without restriction. All data shown in this paper are available online without restriction and at no cost. The WOD is built upon the international exchange of oceanographic data with contributions of data received from many countries. Most of the data shown in this paper and the data within the WOD in which these data reside in a uniform format were gathered under the auspices of the International Oceanographic Data and Information Exchange (IODE) committee of the Intergovernmental Oceanographic Commission (IOC) of UNESCO and the ICSU (International Council of Science) World Data Center system, which is now part of the ICSU World Data System. The WOD contains 112,714 ocean station data casts and 45,003 mechanical bathythermograph profiles for 1939-1945